Perancangan Sistem Informasi Wisata Di Desa Kuto Harjo dengan Metode Agile Berbasis Web - Anjani, Nabila Antania Putri; Jananto, Arief (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
Kuto harjo Village has considerable tourism potential but has not reached the optimal level in managing tourism information so that it can be accessed by tourists and the community. For this reason, an information system must be built that can facilitate access to information about destinations, facilities and tourism activities in the village. This study aims to design and develop a tourism information system in the web-based village of Kuto Harjo using Agile methodology. The Agile methodology was chosen because of its ability to develop repeatable and flexible systems that adapt to changing user needs. This information system will be equipped with features such as tourist destination information, event calendar. The results of this system development are expected to increase tourism information access and support the promotion of tourist destinations in Kuto Harjo Village. Additionally, the implementation of the Agile method in developing this system allows for faster improvements and updates based on user input, so that the system can continue to grow and meet the needs of tourists.